PELETAKAN SITA JAMINAN ATAS HAK KEKAYAAN INTELEKTUAL - Adjie, Ambrosius (Veritas et Justitia, 2015)
This study aims to determine the placement of sequestration of intellectual property rights. This study uses normative research, the research specification descriptive analysis, this research is carried out through the stage of the study of literature, and data analysis conducted qualitative normative. Results of this study show that can be placed sequestration of intellectual property rights, which lies in the economic value of the intellectual property rights.